2017
DOI: 10.1038/s41598-017-10953-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of unique power conversion efficiency of solar cell showing hysteresis in the I-V curve under various light intensities

Abstract: Energy harvesting at low light intensities has recently attracted a great deal of attention of perovskite solar cells (PSCs) which are regarded as promising candidate for indoor application. Anomalous hysteresis of the PSCs a complex issue for reliable evaluation of the cell performance. In order to address these challenges, we constructed two new evaluation methods to determinate the power conversion efficiencies (PCEs) of PSCs. The first setup is a solar simulator based on light emitting diodes (LEDs) allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…8,23,24,[27][28][29][30][31][32][33][34][35][36][37][38][39] Therefore, to extract meaningful information aiming at commercial application, it is necessary to systematically investigate the stability behaviors of actual PVSK solar cells under realistic operational conditions; i.e., under 1 sun illumination with a load for tracking the maximum power point (MPP). [7][8][9][10][40][41][42][43][44][45] On the basis of our survey (Table 1), reported realistic operational long-term stability profiles in PVSK solar cell research is still at an early stage but certainly making progress. At the…”
Section: Introductionmentioning
confidence: 73%
“…8,23,24,[27][28][29][30][31][32][33][34][35][36][37][38][39] Therefore, to extract meaningful information aiming at commercial application, it is necessary to systematically investigate the stability behaviors of actual PVSK solar cells under realistic operational conditions; i.e., under 1 sun illumination with a load for tracking the maximum power point (MPP). [7][8][9][10][40][41][42][43][44][45] On the basis of our survey (Table 1), reported realistic operational long-term stability profiles in PVSK solar cell research is still at an early stage but certainly making progress. At the…”
Section: Introductionmentioning
confidence: 73%
“…On the other hand, if we want to understand the lower light intensity, we have to play with different lower light intensities and different distributions of light (spectra). This is not possible to implement without any optical structures similar to ours (water flow lens [WFL] system with cooling effect, decreasing the light intensity, and modification of the spectrum reaching the surface of the solar device) or some similar construction such as the sun simulator with a wider range of light intensities . When we speak of lower light intensities, then the spectra and their changes are very important, as well as the interaction of light with the environment, which is also sometimes very complex to understand.…”
Section: Introductionmentioning
confidence: 99%
“…This is not possible to implement without any optical structures similar to ours 20,21 (water flow lens [WFL] system with cooling effect, decreasing the light intensity, and modification of the spectrum reaching the surface of the solar device) or some similar construction such as the sun simulator with a wider range of light intensities. 22 When we speak of lower light intensities, then the spectra and their changes are very important, as well as the interaction of light with the environment, which is also sometimes very complex to understand. It should be emphasized here that we found that PV response of the following devices, Sb 2 S 3 -based solar cells made from synthesized doped and undoped material, 20 dye-sensitized solar cells, 21 and silicon solar cells under halogen lamp 23 at a lower light intensity and indoor condition, is superior to that at greater intensities.…”
Section: Introductionmentioning
confidence: 99%
“…However, emerging photovoltaics, for example, a dyesensitized solar cell (DSC), an organic thin-film photovoltaic (OPV), and a perovskite solar cell (PSC) need additional measurement methods because such photovoltaics have the advantage in the case of uses different from that of Si photovoltaics. [3][4][5][6] The performance measurement procedures of such photovoltaics have not been established as an international standard by the IEC. Therefore, characterization of organic photovoltaics tends to be carried out according to the evaluation methods of each institute based on their own methods at the present time.…”
Section: Introductionmentioning
confidence: 99%